High-energy synchrotron x-ray study of deformation-induced martensitic transformation in a neutron-irradiated Type 316 stainless steel - Zhang, Xuan; Xu, Chi; Chen, Yiren; Chen, Wei-Ying; Park, Jun-Sang; Kenesei, Peter; Almer, Jonathan; Burns, Jatuporn; Wu, Yaqiao; Li, Meimei (Acta materialia, 2020)
An unusual tensile deformation behaviour in the form of a propagating band along the sample gauge was observed in two neutron-irradiated 316 stainless steel samples during room-temperature tests, leading to a combination of high strength and high ductility. These bands were not observed in an unirradiated counterpart. With the help of in situ high-energy synchrotron x-ray diffraction, the phase-specific crystal information was tracked at different deformation levels in each sample. Post-irradiation and post-deformation samples were examined using electron microscopy to characterize various microstructural features. All samples displayed a deformation-induced martensitic phase transformation, which was identified as a second strain-hardening mechanism accompanying the dislocation hardening. The deformation-induced martensitic transformation was rationalized by the effect of applied stress on the effective martensite start temperature. The results showed that the irradiation did not alter the dislocation hardening and the martensitic transformation mechanisms, but the increased yield strength in irradiated materials facilitated the localized phase transformation at the onset of plastic deformation, in contrast to the unirradiated material which required pre-straining. The hardening effect of the martensitic transformation reduced the tendency towards necking and mitigated the loss of ductility in the irradiated material by carrying the deformation in the form of a propagating band. Despite the beneficial effect from the martensitic transformation, this study indicates that this mechanism cannot not be activated at typical operating temperatures of nuclear reactors. [Display omitted]